1986
DOI: 10.1203/00006450-198611000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Fetal Plasma Amino Acid Concentrations in the Presence of Maternal Hypoaminoacidemia

Abstract: ABSTRACT. The effects on the conceptus of persistently decreased maternal plasma amino acid concentrations were studied in pregnant rats by the infusion of glucagon (0.21 mglday) to the mother from day 14 to 20 of gestation with a subcutaneous, osmotically driven minipump. Controls received diluent. The experimental animals either had normal caloric intake and weight gain, or diminished caloric intake with no weight gain. Both experimental groups exhibited a decrease in plasma total amino acid concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 28 publications
1
7
1
1
Order By: Relevance
“…Intriguingly, however, neither an enhanced level of ethanol nor any other evident change was seen in the arterial and venous umbilical cord plasma from this mother–infant pair. The same preservation in cord plasma amino acid concentrations was observed in the plasma from rat pups born from dams that had a severe diet-induced depletion of total plasmatic amino acids [33]. This finding is consistent with the previous study of venous umbilical cord plasma by 1 H NMR, wherein ethanol was identified in 5 venous umbilical cord plasma samples, suggesting ethanol to be endogenous.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, however, neither an enhanced level of ethanol nor any other evident change was seen in the arterial and venous umbilical cord plasma from this mother–infant pair. The same preservation in cord plasma amino acid concentrations was observed in the plasma from rat pups born from dams that had a severe diet-induced depletion of total plasmatic amino acids [33]. This finding is consistent with the previous study of venous umbilical cord plasma by 1 H NMR, wherein ethanol was identified in 5 venous umbilical cord plasma samples, suggesting ethanol to be endogenous.…”
Section: Discussionsupporting
confidence: 91%
“…Davenport ML, D'Ercole AJ, Effect of maternal fasting on fetal control pups in our study. indicate enhanced placental transport Of amino acids such that i s , Thissen JP, Triest S, ~oats-staats BM, Underwood LE, Mauerhoff T, Maiter D, availability to the fetus is maintained (57). hi^ might partly…”
mentioning
confidence: 99%
“…This process can be blocked by inhibitors of protein synthesis, demonstrating that increase in transport capacity probably represents the synthesis of new transporter proteins (38). An in vivo study in rats demonstrated maintenance of fetal amino acid concentrations despite prolonged hypoaminoacidemia in the mother, suggesting that a similar process of amino acid transporter protein synthesis might occur in vivo in response to a decrease in circulating amino acid concentrations (39). These results take on added importance relative to observations by Cetin et al (40), who showed, from umbilical blood vessel-sampling data, that in humans the concentration of a-amino nitrogen was lower in maternal and fetal plasma in pregnancies complicated by fetal growth restriction.…”
Section: Amino Acid Transporters On Placentamentioning
confidence: 99%
“…In contrast, fetal O 2 consumption is relatively constant, indicating that a reciprocal relationship may exist, at least over the short term, between glucose oxidation and the oxidation of other energy-producing substrates. In fetal sheep, the leucine oxidation-disposal ratio increases during sustained glucose deficiency, hypoglycemia, and hypoinsulinemia (62), and in fetal rats, sustained hypoglycemia increases protein catabolism and limits fetal growth (39). Thus, at least some amino acids can be diverted from protein synthesis and net protein accretion to protein catabolism and oxidation, either directly or via gluconeogenesis.…”
Section: Fetal Energy Supply Versus Amino Acid Oxidation and Growthmentioning
confidence: 99%